﻿Rapid LC-MS/MS method for determination of scopolamine in human plasma - Anas Alshishani; Inas Hasan; Fatima Ghanayem; Sewar Al-khasawneh; D. F. Chowdhury; Alaa Abu Dayah (Pensoft Publishers, 2022)
Sensitive, simple, and fast LC-MS/MS method for the determination of Scopolamine in human plasma was developed and validated. Liquid-Liquid extraction technique was used for sample preparation. Cyano bonded phase column (150 × 4.6 mm, 5 µm) was used for the separation with an isocratic elution of ammonium format buffer:methanol (60:40) mobile phase at a flow rate of 1 ml.min-1 over 3.8 min run time. Scopolamine and [13C,2H3]-Scopolamine, as internal standard, were detected and quantified in positive ion mode via MRM at m/z 304/138 and m/z 308/142, respectively. The developed method was validated according to FDA and EMA guidelines. The standard calibration curve was linear over the concentration range of 3.03-315.76 pg.ml-1 (r2 = 0.999). The intra-day and inter-day precision was in the range 1.28-10.46% and accuracy 96.89-110.53%. The recovery of analyte and IS was 78.63% and 76.21%, respectively. Scopolamine in plasma was stable at benchtop (short term) for 18 h, in autosampler tray for 43 h, in instrumentation room for 43 h (post-preparative), after 4 freeze-thaw cycles (−70 °C), and 3 days in the freezer (−70 °C). The validated method was successfully applied to a bioequivalence study of scopolamine transdermal patch of 1 mg for 3 days for 16 healthy Jordanian volunteers.